Analysis of occupational health and safety at a maritime warehouse using Hazard Identification, Risk Assessment and Risk Control (HIRARC) - Asep Ridwan; Apriansyah Nuroni; Adelia Adelia; Atia Sonda (Journal Industrial Servicess, 2022)
This study aims to identify and determine risks and risks using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. By conducting prior monitoring and interviewing workers to find out the risks and impacts experienced by workers. Making a HIRARC table by assessing each aspect of hazards, work risks and controls that have been carried out and classifying controls based on 5 hierarchies. Data processing is conducted by analyzing the potential hazards with the HIRARC method. This study identified 12 potential hazards at Gandasari Energy. The findings of 12 risks can be carried out by risk with a hierarchy where there are 5 risk control efforts, including elimination, substitution, engineering control, administrative control, and personal protective equipment. Of the 12 potential hazards, many workers still do not use Personal Protective Equipment (PPE). The importance of PPE is to minimize the occurrence of work accidents.